The Clinicopathological Distinction Between Seropositive and Seronegative Immune-Mediated Necrotizing Myopathy in China - Ma, Xue; Xu, Li; Ji, Suqiong; Li, Yue; Bu, Bitao (Frontiers in Neurology, 2021)
Objectives: The present study aimed to compare the clinicopathological features of patients with seronegative immune-mediated necrotizing myopathy (IMNM) and those positive for anti-signal recognition particle (SRP) or anti-3-hydroxy-3-methylglutarylcoenzyme-a reductase (HMGCR) antibodies. Methods: We retrospectively analyzed the data of patients with IMNM treated in the Neurology Department of Tongji Hospital from January 1, 2013, to December 31, 2019. Results: Among the 117 patients with IMNM, 30.8% (36/117) were positive for anti-SRP antibodies, 6.0% (7/117) were positive for anti-HMGCR antibodies, and 13.7% (16/117) were seronegative. Myalgia at presentation (62.5 vs. 23.3%, p = 0.0114) was more commonly observed in patients with seronegative IMNM than in those with seropositive IMNM. Subclinical cardiac involvement was more frequently detected in seronegative IMNM than in seropositive IMNM (6/13 vs. 5/33, p = 0.0509, echocardiogram; 7/7 vs. 12/24, p = 0.0261, cardiac MRI). Deposition of membrane attack complex (MAC) on the sarcolemma of myofibers in biopsied muscle was less commonly observed in patients with seronegative IMNM than in patients with seropositive IMNM (16.7 vs. 68.2%, p = 0.0104). The rate of marked improvement following immunotherapy tended to be higher in patients with seronegative IMNM than in those with seropositive IMNM (87.5 vs. 61%, p = 0.0641). Conclusions: Patients with seronegative IMNM more frequently present with myalgia at onset, exhibit more subclinical cardiac involvement and uncommon MAC deposition on myofibers, and experience better outcomes than those with seropositive IMNM.